Conceptualizing community resilience to natural hazards – the emBRACE framework - Forrester, John Martin; Kruse, Sylvia; Abeling, Thomas; Deeming, Hugh; Fordham, Maureen; Forrester, John; Jülich, Sebastian; Karanci, A. Nuray; Kuhlicke, Christian; Pelling, Mark; Pedoth, Lydia; Schneiderbauer, Stefan (Natural Hazards and Earth System Sciences, 2017)
Abstract. The level of community is considered to be vital for building disaster resilience. Yet, community resilience a s a scientific concept often remains vaguely defined and lacks the gui ding characteristics necessary for analysing and enhancing resilience on the ground. The emBRACE framework of community resilience presented in this paper provides a heuristic analytical tool for understanding, explaining and measuring community resilience to natural hazards. It was developed in an iterative process building on existing scholarly d ebates, on empirical case study work in five countries and on particip atory consultation with community stakeholders where the framework was applied and ground-tested in different contexts and for different haz ard types. The framework conceptualizes resilience across three core d omains: (i) resources and capacities, (ii) actions and (iii) learning. These three domains are conceptualized as intrinsically conjoined wit hin a whole. Community resilience is influenced by these integral elem ents as well as by extra-community forces comprising disaster risk gov ernance and thus laws, policies and responsibilities on the one hand a nd on the other, the general societal context, natural and human-made disturbances and system change over time. The framework is a graphical ly rendered heuristic, which through application can assist in guiding the assessment of community resilience in a systematic way and identi fying key drivers and barriers of resilience that affect any particula r hazard-exposed community.